The production of western Greek amphorae in Agrigento (Southern Sicily): An archaeometric and archaeological characterisation of the late 6th-4th centuries BCE series. (October 2022) - Montana, G.; Randazzo, L.; Gasparo Morticelli, M.; Baldoni, V.; Bechtold, B.
Highlights: Analysis of western Greek amphorae produced at Agrigento in late Archaic and Classical period. Comparison with raw clay materials available in the area and local ceramics productions. Definition of a chemical reference group by the analysis of overfired kiln wastes, archaeological ceramics and local clayey materials. New insights for a better understanding of the colony's economic development. Abstract: This paper aims at an interdisciplinary, archaeological and archaeometric characterisation of the western Greek amphorae series produced in late Archaic and Classical-period Agrigento (southern Sicily). The research is based on a macroscopic examination, according to the standardised methods of Fabrics of the Central Mediterranean (FACEM), combined with petrographic analyses of 21 amphorae samples of presumed local fabric found in Agrigento itself. These were found in the artisanal area outside Porta V, in the excavations South of the temple of Zeus, and in several Sicilian consumption sites. Furthermore, a selection of 12 coarse ware samples and three tiles, all of supposed local manufacture and unearthed in Agrigento, has been investigated. For comparison, 12 raw clays sampled in the gullies between the Tempio di Giunone and the Tempio della Concordia have been included in this study and are complimented by chemical analyses (ICP-MS and ICP/OES) undertaken on a group of 19 ceramic samples and seven raw materials. As a result, our study confirms the local manufacture of the entire selection of 36 ceramic samples and the more than acceptable petrographic and chemical homogeneity of the ceramic pastes produced with locally sourced clays. The identification of a production of western Greek wine (?) amphorae in Agrigento dating from the late 6th-4th century BCE breaks ground for a better understanding of the colony's economic development during the late Archaic and Classical periods. The city has to be regarded, in fact, as one of the major global players within the wider frame of Sicilian commercial interaction, especially during the 5th century BCE.